The interrelationships among motor competence, physical activity and health-related fitness in the early years - King-Dowling, Sara (My University, 2018)
Motor competence is positively associated with physical activity and health-related fitness (HRF) across childhood and adolescence. Owing to their motor difficulties, children with Developmental Coordination Disorder (DCD) are found to have poorer HRF and lower activity levels compared to typically developing (TD) children. It is thought that children with DCD are less physically fit due in part to hypoactivity; however, it is still unclear how young these deficits emerge, or if physical activity explains these HRF differences. This thesis aims to fill these gaps by examining physical activity and HRF in preschool children with and without DCD, and testing mediation models linking motor competence to HRF through physical activity engagement, both cross-sectionally and over time from preschool to school age. The first and second studies demonstrated that preschool children with DCD exhibit poorer musculoskeletal and aerobic fitness compared to TD children, however physical activity engagement was similar and did not explain these fitness deficits. The third study found that the relationship between motor competence and physical activity was not significant at preschool age, but emerged over time as children reached school age. Additionally, motor competence was a significant positive predictor of musculoskeletal fitness across the early years, again largely independent of physical activity levels. This thesis represents the first comprehensive series of studies that examines objectively-measured motor competence, physical activity and HRF in large samples of preschool-age children both with and without DCD. These studies highlight that poor motor competence is a risk factor for poor physical fitness, irrespective of physical activity in the early childhood period. Early motor interventions may positively influence physical fitness and may help to prevent the declines in physical activity observed as children with DCD reach middle childhood and adolescence.
Motor competence, physical activity and fitness in childhood
Keywords: Developmental Coordination Disorder; preschool; accelerometry; musculoskeletal fitness; aerobic fitness; physical activity; children; motor competence